Abuso e repressão: fibras do mesmo fio na infância das meninas de Helena Parente Cunha - Lílian Almeida de Oliveira Lima (Estudos de Literatura Brasileira Contemporânea)
The narrative production of Brazilian writer Helena Parente Cunha is marked by the presence of female characters and the questioning of this universe, shaking structures and hegemonic standards. Young and adult women are the main characters of her plots, but the girls also take part in the complaint about the pain and the oppression imposed by culturally - established patterns. In this article, short stories of the books Os provisórios , Cem mentiras de verdade and Falas e falares are discussed, analyzing the situations of abuse and repression to which children are su bjected, and the demarcations of gender present there. These characters are subjected to a series of oversights that undermines the idealized notion of childhood as a lost paradise. In the course of analysis the ideas of Neil Postman about narrowing the li mits that differentiate adults and children are used, as well as the notion of „privatization of childhood‟, pointed out by Jacinto Sarmento.